Mujeres Magazine as a Classifying Space of the Performativities of Being a Woman in Cuba - Fernández-Silva, Luis Alberto; Ulloa Guerra, Óscar; Sartor-Harada, Andresa; Martínez-Sierra, Ricel (Journalism Practice, 2023)
This article analyzes the journalistic discourse of the Cuban magazine Mujeres between the years 2010–2015, by questioning its thematic agenda as a dynamic resource for meanings. The main objective of the study is to understand the singular knowledge produced about the experience of women in the economic spheres in Cuba. For this, the qualitative research crosses the meanings produced about the participation of Cuban women by journalistic narratives with the specific characteristics of the productive scenarios where they act, thus revealing how Mujeres promotes particular readings of those contexts and their subjects. The asymmetry in the visualization between the state and non-state economic spheres, the politicization of women's roles in non-state productive scenarios and the disregard of other forms of participation of Cuban women, are among the main results achieved. These limits of the constructed meanings allow us to understand how the journalism of the magazine operates as a classifying device of being a woman in Cuba.
Keywords: magazine journalism; women; production of meanings; gender representations; being a woman; Cuba; Scopus; JCR